Physicians and the Production of Health: Returns to Health Care during the Mortality Transition - Helge Liebert; Beatrice Mäder (Institute of Labor Economics (IZA), 2022)
This paper investigates the returns to health care provision during the mortality transition. We construct a new panel data set covering German municipalities from 1928 to 1936. The endogeneity of health care supply is addressed by using the expulsion of Jewish physicians from statutory health insurance as exogenous variation in regional physician supply. Increases in the supply of physicians reduce infant mortality and mortality from common childhood diseases. Using a semiparametric control function approach, we find diminishing marginal returns to health care provision. The results are consistent with historical trends in infant mortality over the 20th century.
Keywords: I10; I18; N34; 330; infant mortality; physicians; health care supply; mortality transition; semiparametric IV